2023
DOI: 10.1038/s41598-023-33973-8
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state oscillations reveal disturbed excitation–inhibition ratio in Alzheimer’s disease patients

Abstract: An early disruption of neuronal excitation–inhibition (E–I) balance in preclinical animal models of Alzheimer’s disease (AD) has been frequently reported, but is difficult to measure directly and non-invasively in humans. Here, we examined known and novel neurophysiological measures sensitive to E–I in patients across the AD continuum. Resting-state magnetoencephalography (MEG) data of 86 amyloid-biomarker-confirmed subjects across the AD continuum (17 patients diagnosed with subjective cognitive decline, 18 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 88 publications
1
11
1
Order By: Relevance
“…The balance between neural excitation and inhibition can be estimated from resting state MEG and/or EEG data by computing the aperiodic exponent of the signal. This method was validated with simulated local field potentials [ 24 ], and applied to AD patients by van Nifterick and colleagues [ 20 ], reporting signs of hyperexcitability in demented patients with AD but not in early-stage patients, which is fully consistent with our findings. Our approach is complementary to that of van Nifterick et al, as it is based on a different imaging neuroimaging modality.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The balance between neural excitation and inhibition can be estimated from resting state MEG and/or EEG data by computing the aperiodic exponent of the signal. This method was validated with simulated local field potentials [ 24 ], and applied to AD patients by van Nifterick and colleagues [ 20 ], reporting signs of hyperexcitability in demented patients with AD but not in early-stage patients, which is fully consistent with our findings. Our approach is complementary to that of van Nifterick et al, as it is based on a different imaging neuroimaging modality.…”
Section: Discussionsupporting
confidence: 87%
“…While our model did not directly assess the balance between neural excitation and inhibition, previous research supports the choice of modeling changes in local inhibition in AD and bvFTD patients [ 9 , 11 , 18 , 20 , 21 ]. In turn, our results provide support for the hypothesis that alterations in neural inhibition modulated by disease-specific atrophy patterns can underlie changes in functional connectivity measured in neurodegeneration.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Higher values correspond to higher E/I. Recently, it has been demonstrated that this approach is sensitive to E/I alterations known to occur in Alzheimer Disease (Van Nifterick et al 2023). The computation of DFA-based E/I was performed in alpha band, following the method described in (Van Nifterick et al 2023) and based on an adaptation for Brainstorm of the code available at https://github.com/annevannifterick/fEI_in_AD;…”
Section: Methodsmentioning
confidence: 99%
“…Compared to previous studies using the specparam algorithm, where frequency range varies, many used 40 Hz as the upper frequency range 23,48,61 . For sake of clarity, using 48 Hz as upper frequency is also a widely adopted option 62,63 , and stays within the recommendations of the algorithm’s authors. All participants showed a discernible alpha peak in the PSD (see an example in Figure 1).…”
Section: Methodsmentioning
confidence: 99%